LEVEL OF KNOWLEDGE AND PERSONAL GENITAL HYGIENE BEHAVIORS WITH THE DEGREE OF VAGINAL DISCHARGE IN ADOLESCENT GIRLS - Auriel Jasmine; Shinta Wahyusari; Rif'atul Fani (HEARTY, 2026)
Vaginal discharge is a reproductive health problem that is often experienced by adolescent girls, but is often considered normal so it is not taken seriously. In fact, vaginal discharge can be a sign of certain diseases so good knowledge is needed to prevent the risks. Increasing knowledge and behavior of genetically modified personal hygiene is important to form adolescent awareness in maintaining the cleanliness of the reproductive organs. This study aims to determine the relationship between the level of knowledge and personal hygiene genetalia with the degree of vaginal discharge in adolescent girls. This study used a cross sectional analytical design with a research sample consisting of 182 adolescent girls in grades 7 and 8 at SMPN 1 Wajak. Data collection was carried out using a questionnaire, then the data was analyzed using a Gamma statistical test. The research instruments used were based on indicators of knowledge, personal hygiene behavior, and degree of vaginal discharge. The results of this study show that there is a relationship between the level of knowledge and vaginal discharge in adolescent girls with a ρ value of 0.011 and there is also a relationship between genetic personal hygiene behavior and the degree of vaginal discharge in adolescent girls with a ρ value of 0.042. These findings indicate that adolescent girls' understanding of vaginal discharge and genetic personal hygiene behaviors still needs to be improved, so schools and health workers need to strengthen reproductive education, and further research is recommended to develop.